A community-based screening campaign for the detection of diabetes mellitus and hypertension in the eastern province, Saudi Arabia: Methods and participation rates - Ageel J Al-Ghamdi; Khalid A Al-Turki; Nadira A Al-Baghli; Ahmad G El-Zubaier (Wolters Kluwer Medknow Publications, 2007)
Objective: To describe a community-based diabetes and hypertension screening campaign, the percentage of screened positive individuals, identified the participation rate, and the factors affecting the participation. Campaign design and methods: A community-based screening campaign whose main objective was the screening for diabetes and hypertension was conducted in the Eastern Province of Saudi Arabia for three and half months in the year 2004. A structured questionnaire was used. Diabetes mellitus was diagnosed on the basis of repeated detection of a fasting blood sugar equal to or more than 126 mg/dl, and hypertension when the blood pressure was 140/90 mm Hg or more.. Results: Of the 650,000 target population, 214,381 (33%) participated, and 197,681 questionnaire were completed. Of the number of individuals screened, 31,711 (16%) were positive for abnormal blood pressure and /or glucose, and needed confirmation of their results. Only 17296 (54.5%) of them were referred to health facilities for confirmation of results Conclusion: Community screening campaigns for diabetes mellitus and hypertension is extremely efficient in identifying undiagnosed diabetic and hypertensive individuals. The most successful strategy for the screening and confirmation of results was through PHCCs, especially in the rural areas, where there was good organization and strict adherence to guidelines on methodology.